Genetics of Frontotemporal Lobar Degeneration - Galimberti, Daniela; Scarpini, Elio (Frontiers in Neurology, 2012)
Frontotemporal lobar degeneration (FTLD), the most frequent neurodegenerative disorder with a presenile onset, presents with a spectrum of clinical manifestations, ranging from behavioral and executive impairment to language disorders and motor dysfunction. Familial aggregation is frequently reported, and about 10% of cases have an autosomal dominant transmission. Microtubule associated protein tau (MAPT) gene mutations have been the first ones identified and are associated with early onset behavioral variant frontotemporal dementia phenotype. More recently, progranulin gene (GRN) mutations were recognized in association with familial form of FTLD. In addition, other genes are linked to rare cases of familial FTLD. Lastly, a number of genetic risk factors for sporadic forms have also been identified. In this review, current knowledge about mutations at the basis of familial FTLD will be described, together with genetic risk factors influencing the susceptibility to FTLD.